Financial stability challenges in candidate countries - managing the transition to deeper and more market-oriented financial systems - Thierry Bracke; André Geis; Maurizio Habib; Csaba Móré; Éva Katalin Polgár; Adalbert Winkler; Emidio Cocozza; Peter Backé (European Central Bank (ECB), 2008)
This paper reviews financial stability challenges in the EU candidate countries Croatia, Turkey and the former Yugoslav Republic of Macedonia. It examines the fi nancial sectors in these three economies, which, while at very different stages of development and embedded in quite diverse economic settings, are all in a process of rapid financial deepening. This manifests itself most clearly in the rapid pace of growth in credit to the private sector. This process of financial deepening is largely a natural and welcome catching-up phenomenon, but it has also increased the credit risks borne by the banking sectors in the three economies. These credit risks are compounded by the widespread use of foreign currency-denominated or -indexed loans, leaving unhedged bank customers exposed to potential swings in exchange rates or foreign interest rates. Moreover, these financial risks form part of a broader nexus of vulnerabilities in the economies concerned, in particular the external vulnerabilities arising from increasing private sector external indebtedness. That said, the paper also fi nds that the authorities in the three countries have taken several policy actions to reduce these fi nancial and external vulnerabilities and to strengthen the resilience of the financial sectors.
Keywords: F32; F41; G21; G28; 330; Europe; banking sector; vulnerability indicators; capital inflows; emerging markets.; Finanzsektor; Bankenreform; Kreditgeschäft; Kapitalimport; Schwellenländer; Systemtransformation; Kroatien; Mazedonien; Türkei